2009
DOI: 10.1080/01468030802213637
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Converter Using Semiconductor Optical Amplifier Mach-Zehnder Interferometer Based on XPM at 40 Gb/s for Future Transport Networks

Abstract: We have simulated, for the first time, wavelength converter for future broadcast networks at 40 Gb/s using low-cost semiconductor optical amplifiers. The performance analysis is carried out for an all-optical frequency converter based on cross-phase modulation in two semiconductor optical amplifiers arranged in a MachZehnder interferometer configuration to evaluate the efficiency of conversion. The results, evaluated analytically for input, return to zero signal at a bit rate of 40 Gb/s show that conversion is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…The concept of optical encoding is shown in Figure 1 below. From the study [11,12], we have developed a scheme which also controls the multiple access interference with help of modulation, encoding, EDFA and coupler for optical networks. The basic structure for the proposed scheme has been displayed in Figure 2 below.…”
Section: Multiple Hop and Multiple User Architecturementioning
confidence: 99%
“…The concept of optical encoding is shown in Figure 1 below. From the study [11,12], we have developed a scheme which also controls the multiple access interference with help of modulation, encoding, EDFA and coupler for optical networks. The basic structure for the proposed scheme has been displayed in Figure 2 below.…”
Section: Multiple Hop and Multiple User Architecturementioning
confidence: 99%
“…Their results show that conversion is possible over a wavelength separation of 1 nm between the pump and the input wavelength. They have demonstrated that increasing the driving current can decrease the XPM effect and the XGM scheme shows extinction ratio degradation for conversion to longer wavelengths [3].…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…SOA-delayed interference configuration [1]. Furthermore, Randhawa et al [3] have simulated wavelength converter for future broadcast networks at 40 Gbit/s using low-cost SOAs. Their performance analysis is carried out for an all-optical frequency converter based on XPM in two SOAs arranged in a Mach-Zehnder interferometer (MZI) configuration to evaluate the efficiency of conversion.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
See 2 more Smart Citations